2016
DOI: 10.1016/j.seares.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Common trends in German Bight benthic macrofaunal communities: Assessing temporal variability and the relative importance of environmental variables

Abstract: We examined long-term variability in the abundance of German Bight soft bottom macro-zoobenthos together with major environmental factors (sea surface temperature, winter NAO index, salinity, phosphate, nitrate and silicate) using one of the most comprehensive ecological long-term data sets in the North Sea . Two techniques, Min/Max Autocorrelation Factor Analysis (MAFA) and Dynamic Factor Analysis (DFA) were used to identify underlying common trends in the macrofaunal time series and the relationships between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 65 publications
(97 reference statements)
1
10
0
Order By: Relevance
“…In the North Sea, the key environmental parameter controlling benthic macrofauna composition is wintertime temperature (Beukema et al, 2000;Kröncke et al, 1998Kröncke et al, , 2013Kröncke et al, , 2001Neumann et al, 2008;Shojaei et al, 2016). Our results suggest similar processes occurring in the NW Mediterranean under hydro-sedimentary forcing.…”
Section: Key Environmental Parameters Involvedsupporting
confidence: 52%
See 2 more Smart Citations
“…In the North Sea, the key environmental parameter controlling benthic macrofauna composition is wintertime temperature (Beukema et al, 2000;Kröncke et al, 1998Kröncke et al, , 2013Kröncke et al, , 2001Neumann et al, 2008;Shojaei et al, 2016). Our results suggest similar processes occurring in the NW Mediterranean under hydro-sedimentary forcing.…”
Section: Key Environmental Parameters Involvedsupporting
confidence: 52%
“…Regarding the most appropriate integration period, it was first suggested that NAO has a stronger control on the climate of the Northern Hemisphere during wintertime. During this season, the magnitude and spatial coherence of atmospheric circulation variability as well as the influence of circulation changes and large-scale precipitation are stronger (Osborn, 2006;Osborn, Conway, Hulme, Gregory, & Jones, 1999 (Kröncke et al, 1998(Kröncke et al, , 2001Kröncke, Reiss, & Dippner, 2013), in the German Bight (Neumann, Ehrich, & Kröncke, 2008;Shojaei et al, 2016), and in the Wadden Sea (Beukema, Essink, & Dekker, 2000…”
Section: Nao and Wemo Indices Integration Periodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for the hydroclimatic shift in 2014 no congruent changes in taxonomic and trait-based structures were found. The regimes and shifts in taxonomic and trait-based long-term variability, found in the study area, corresponded to shifts and changes, which were detected in the whole marine and North Sea ecosystem [49, 94, 95].…”
Section: Discussionmentioning
confidence: 92%
“…Significant long-term changes to taxonomic community variability in marine ecosystems have been documented worldwide [4143], including in North Sea pelagic [4446] and benthic [4749] communities.…”
Section: Introductionmentioning
confidence: 99%